The Mapu perspective of judicial spaces and Mapuche geographical thinking - De La Ossa Arias, Leonarda (2019)
The article explores the Mapu perspective, from an ethnographic immersion with Pu Mapuche, around a judicial space, which moves in an antagonistic relation with the geographical spaces in the plural, presenting tensions that open up other non-hegemonic geographies, which they escape the centrality of vindicating geography as the science of the space of man, displacing reflection, towards the coexistence of the beings and all forms of life of and in the spaces, as said and practiced by the thinkers of indigenous peoples Quidel (2012), Melin et at (2017).